Masjid Kampung Pantai Chenor, Temerloh, Pahang / [lukisan teknik] - 175258 Abdul Rahim Adam (Kuala Lumpur : Universiti Teknologi Malaysia, 1982)
Kajian Lukisan Teknik (Jabatan Senibina) - Universiti Teknologi Malaysia, 1982